Adult day services: a potential antidote to social isolation and loneliness in marginalized older adults - Sadarangani, Tina; Fernandez Cajavilca, Moroni; Qi, Xiang; Zagorski, William (Frontiers in Public Health, 2024)
Loneliness and social isolation affect more than 1 in 4 community-dwelling older adults in the United States, who may also require long-term care support. Despite being seen as a solution to the long-term care crisis, most older adults prefer to age in place rather than using skilled nursing facilities. However, in-home care is unsustainable due to a shortage of direct care workers and may exacerbate social isolation by confining older adults to their homes. Adult Day Services (ADS) addresses both issues. ADS provides care to adults with physical, functional, and or cognitive limitations in non-residential, congregate, community-based settings. ADS also provides daily cognitive and physical stimulation, often with medical support, in a social and supported environment, centered around the needs and preferences of participants. Before the COVID-19 pandemic, nearly 5,000 ADS centers were widely available. However, with limited public support, the ADS industry has struggled as demand by the growing number of older adults and families need health and social support. The ADS industry must be recognized for its unique ability to buffer social isolation and loneliness in chronically ill older adults while serving as an effective platform for chronic disease management. This perspective piece highlights the critical role of ADS centers in reducing loneliness and social isolation and promoting healthy equity. We also explore the benefits of ADS, the financial, policy, and societal barriers to utilizing ADS, and the potential solutions to ensure its sustainability and growth.